2007
DOI: 10.1080/03655230701596392
|View full text |Cite
|
Sign up to set email alerts
|

Acute sensorineural hearing loss associated with aortitis syndrome

Abstract: In both patients, hearing loss involved the cochlea and hearing recovered following corticosteroid treatment. A literature review revealed that hearing loss was commonly manifested in middle-aged females and involved bilateral ears. Corticosteroid treatment was effective in improving hearing in most episodes in the previously reported cases as in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Only a few cases in the literature reported an association of TA with SNHL [ 82 84 ]. Hearing loss is often progressive, although it can be stable or fluctuating; is usually bilateral and asymmetric; develops over several weeks to months; and mainly involves high frequencies.…”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
“…Only a few cases in the literature reported an association of TA with SNHL [ 82 84 ]. Hearing loss is often progressive, although it can be stable or fluctuating; is usually bilateral and asymmetric; develops over several weeks to months; and mainly involves high frequencies.…”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
“…Kanzaki et al [10] reported six cases of steroiddependent SNHL associated with TAK. Yasui and Yamasoba [9] also reported that corticosteroid therapy was effective in improving the hearing in 14 out of 20 cases of SNHL associated with TAK. In our case, although corticosteroid therapy was ineffective after the onset of severe bilateral hearing loss, antecedent Meniere's disease-like symptoms seemed to be partially controlled with prednisolone and methotrexate.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible cause is the immune-mediated inflammatory process in the membranous labyrinth [5,9]. Kanzaki et al [10] reported six cases of steroiddependent SNHL associated with TAK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations